Analisis Pengaruh Kualitas Produk, Kualitas Layanan, Harga, Dan Lokasi Terhadap Keputusan Pembelian Di Rumah Makan Gule Kepala Ikan Mas Agus Surakarta - Anggoro, Ganang Bagus; , Drs. Wiyadi, M.M., Ph.D (2015)
The purpose in this research is analyzing the influence of product quality of the decision purchases in Gule Kepala Ikan Mas Agus Surakarta. Analyze the influence of the quality of services of the decision purchases in Gule Kepala Ikan Mas Agus Surakarta. Analyze the influence the price of the purchase decision in Gule Kepala Ikan Mas Agus Surakarta. Analyze the influence of the location of the decision purchases in Gule Kepala Ikan Mas Agus Surakarta. Population in this study was all the consumers who buy Gule Kepala Ikan Mas Agus in Surakarta while sample used as many as 100 responden. The sample collection that is used is purposive sampling. An instrument the analysis used is a test of normality, multicolinearity test, heteroskedastisitas test, a coefficient test determination (r2), f (test the accuracy of test model) and test t (test a hypothesis). Based on the data analysis known variable quality products influential positive and significant purchase decision, this means that the higher the perception of consumers on the quality of products, it will be getting stronger encourage consumers to make purchase decisions. Variable quality of service influential positive and significant purchase decision, this means that the higher the perception of consumers on the quality of service, it will be getting stronger encourage consumers to make purchase decisions. The price of a variable effect on the purchase decision , this means that the higher assessment of consumers on the price of , it will further strengthen the consumer to make a purchase decisions. Variable effect on the location of the purchase decision, this means that the higher assessment of consumers on the location, it will further strengthen the consumer in doing the purchase decisions. The value of r square (r2) 0,524 obtained by. This means that variations change can be explained by the decision of the purchase of variable (X1) quality products, the quality of services (X2), the price (X3) and location (X4) 52,4%. While the rest of 47.6% described by other variables beyond the model. Keywords: Quality of products, Quality of service, price, location and purchase decision.